A Low Cost Implantation Model in the Rat That Allows a Spatial Assessment of Angiogenesis - Slezak, Paul; Slezak, Cyrill; Hartinger, Joachim; Teuschl, Andreas Herbert; Nürnberger, Sylvia; Redl, Heinz; Mittermayr, Rainer (Frontiers in Bioengineering and Biotechnology, 2018)
There is continual demand for animal models that allow a quantitative assessment of angiogenic properties of biomaterials, therapies, and pharmaceuticals. In its simplest form, this is done by subcutaneous material implantation and subsequent vessel counting which usually omits spatial data. We have refined an implantation model and paired it with a computational analytic routine which outputs not only vessel count but also vessel density, distribution, and vessel penetration depth, that relies on a centric vessel as a reference point. We have successfully validated our model by characterizing the angiogenic potential of a fibrin matrix in conjunction with recombinant human Vascular Endothelial Growth Factor (rhVEGF165). The inferior epigastric vascular pedicles of rats were sheathed with silicone tubes, which were subsequently filled with 0.2 ml of fibrin and different doses of rhVEGF165, centrically embedding the vessels. Over four weeks, tissue samples were harvested and subsequently immunohistologically stained and computationally analyzed. The model was able to detect variations over the angiogenic potentials of growth factor spiked fibrin matrices. Adding 20 ng of rhVEGF165 resulted in a significant increase in vasculature while 200 ng of rhVEGF165 didn’t improve vascular growth. Vascularized tissue volume increased during the first week and vascular density increased during the second week. Total vessel count increased significantly and exhibited a peak after 2 weeks which was followed by a resorption of vasculature by week four. In summary, a simple implantation model to study in vivo vascularization with only a minimal workload attached was enhanced to include morphologic data of the emerging vascular tree.